Incongruence between women's survey‐ and interview‐determined decision control preferences: A mixed methods study of decision‐making in metastatic breast cancer. Issue 8 (22nd May 2018) - Ejem, Deborah; Dionne‐Odom, J. Nicholas; Turkman, Yasemin; Knight, Sara J.; Willis, Dan; Kaufman, Peter A.; Bakitas, Marie
Abstract: Objective: Women with metastatic breast cancer face numerous, complex treatment and advance care planning (ACP) decisions. Our aim was to develop a better understanding of women with metastatic breast cancer's decision‐making preferences overtime and relative to specific types of decisions. Methods: Convergent, parallel mixed‐methods study. Participants completed the Control Preferences Scale (CPS) and a semi‐structured interview of decision‐making experiences at enrollment (T1; n = 22) and when facing a decision or 3 months later (T2; n = 19). We categorized women's decision‐making experience descriptions into one of the CPS decisional styles and compared them to their CPS response. We constructed an analytic grid that aligned the interview‐determined treatment and ACP decisional preferences with the CPS categories at T1 and T2 and calculated Cohen's kappa coefficient and congruence percentages. Results: Participants ( n = 22) were White (100%), averaged 62 years, married (54%), retired (45%), and had a bachelor's degree (45%). Congruence between CPS response and interview‐determined treatment preferences at T1 was 32% (kappa = 0.083) and 33% (kappa = 0.120) at T2. Congruence between CPS survey response and interview‐determined ACP preferences at T1 was 22.7% (kappa =0.092) at T1 and 11% (kappa = 0.011) at T2. Conclusions: Although women selected a "shared" treatment decision‐making style using the CPS validated tool, when interviewed their descriptions generally reflected a passive process in which they followed the oncologists' treatment suggestions. Future research should explore whether the incongruence between stated and actual decision‐making style is a function of misinterpreting the CPS choices or a true inconsistency that could lead to adverse consequences such as decisional regret.